EVALUASI PROGRAM BANTUAN ALAT TANGKAP PERIKANAN DALAM UPAYA MENDORONG PENINGKATAN PRODUKSI DAN EKONOMI KELOMPOK NELAYAN DI KECAMATAN PAKUHAJI KABUPATEN TANGERANG - Akbar Roydinata; Ipah Ema Jumiati (stiatabalong.ac.id, 2025)
The fishing gear assistance program is a program that supports fishermen to increase fishermen's productivity and income in fishing activities. The problems that occur and are studied by researchers are that the fisheries fishing gear assistance program has not achieved maximum production and production value, as well as the limited number of fishing vessels to maximize production results and production value in Pakuhaji District. This research aims to find out how to evaluate the results of the implementation of the fishing gear assistance program in Pakuhaji District. The focus of this research is the results of the implementation of the fishing gear assistance program which aims to increase production and the economy of fishing groups. This research uses qualitative methods by analyzing the results of interviews with 9 (nine) informants, observation, documentation and document study. Data were analyzed with 6 (six) indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness, accuracy. The results of this research indicate that the results of the implementation of the fishing gear assistance program can be said to be quite good in its implementation. However, there are still obstacles in the amount of fishing equipment assistance distributed to the Joint Business Group (KUB) which is still not sufficient to be distributed evenly to KUB members and the assistance provided is not sufficient to overcome the problems existing in KUB. So the Fishing Equipment Assistance Program in Pakuhaji District, Tangerang Regency has not been fully implemented well and optimally. It is necessary to adjust the amount of fishing equipment assistance when handing over assistance to each Joint Business Group (KUB), so that the assistance provided can be felt by all KUB members. Keywords : Evaluation, Program, Fishing Gear Assistance